PENERAPAN MEDIA LEMBAR KERJA SISWA DAN QUIZ DALAM MENINGKATKAN HASIL BELAJAR SISWA MATERI PENDAPATAN NASIONAL PADA KELAS X SMA NEGERI 10 SEMARANG TAHUN PELAJARAN 2011-2012 - Muliawati, Weni (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The objectives of the study are (1) to know studentsâ motivation in understanding the materials of National Income, (2) to improve studentsâ study result on the materials of National income. It was a class action research which was conducted in 2 cycles. The subject of the study was 31 students of X-3 in SMA N 10 Semarang. The data were collected by test and observation and then analyzed by percentage description. The result of the study showed that the averageÂ of success levelÂ in the 1st cycle was 73.31% and in the 2nd cycle was 78.67% so it rose 5.26% from the 1st cycle to the 2nd cycle and the criterion level of teaching completeness was 93.14%